Analysis Of Ethical Interpersonal Communication Patterns (Between Superiors And Subordinates) In Family-Owned Small And Medium Enterprises And Their Impact On Job Satisfaction - Eva Trisnawati; Muhammad Nur Abdi (Citakonsultindo, 2025)
This study analyzes patterns of ethical interpersonal communication between supervisors and subordinates in family-owned MSMEs and their impact on job satisfaction. Using a descriptive qualitative approach, the research was conducted in three family-owned MSMEs in Makassar through in-depth interviews and observations. The findings reveal four dominant communication patterns: ethical–paternalistic, family–collaborative, hierarchical–flexible, and egalitarian–transparent. Ethical communication that emphasizes openness, honesty, and empathy is proven to enhance job satisfaction; however, the duality of family and professional roles creates challenges such as perceptions of favoritism and boundary ambiguity. This study recommends the establishment of formal communication protocols that preserve family values.